2021
DOI: 10.3390/foods10071672
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for Mild Cognitive Impairment and Alzheimer’s Disease: A Systematic Review and Meta-Analysis

Abstract: Accumulating evidence from animal studies supports the potential role of probiotics and prebiotics in alleviating neurodegenerative diseases. However, whether dietary supplementation with probiotics improves cognitive function in patients with Alzheimer’s disease (AD) or mild cognitive impairment (MCI) is unclear. We searched literature databases for relevant randomized control trials and compared the outcomes between control/placebo and intervention groups. The results of the included studies were meta-analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 40 publications
1
35
0
1
Order By: Relevance
“…Another strategy includes the use of prebiotics (often fiber supplements) aimed to promote the growth of certain microbes, or probiotics, supplements of beneficial strains ( 59 ). A meta-analysis showed positive effects on cognition of Bifidobacterium and Lactobacillus probiotics in patients with MCI ( 60 ). However, beneficial butyrate-producing species are often strictly anaerobic or oxygen sensitive, complicating culturing and probiotic production ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy includes the use of prebiotics (often fiber supplements) aimed to promote the growth of certain microbes, or probiotics, supplements of beneficial strains ( 59 ). A meta-analysis showed positive effects on cognition of Bifidobacterium and Lactobacillus probiotics in patients with MCI ( 60 ). However, beneficial butyrate-producing species are often strictly anaerobic or oxygen sensitive, complicating culturing and probiotic production ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a randomized, double-blind, and controlled trial with 46 AD patients administered a probiotic mixture for 12 weeks did not find any significant difference in any of the outcomes measured that included cognitive, inflammatory, and oxidative biomarkers [ 217 ]. Still, a recent systematic review and meta-analysis revealed an effect of probiotics on cognitive function in people with mild cognitive impairment and to a lesser extent in AD patients, associated with the number of microorganisms added to the probiotic mixture, the dosage and duration of the intervention, and the severity of the disease [ 218 ].…”
Section: Microbiota-based Interventionsmentioning
confidence: 99%
“…The results of the recent meta-analysis supplied confirmation that sufficient probiotic supplementation over a longer period of time might enhance cognitive function [ 132 ]. Within this context, a prolonged 12-week administration of 200 mL/day of milk infused with probiotics ( L. acidophilus , L. casei , B. bifidum , and L. fermentum ) in a concentration of 2 × 10 9 CFU to the patients with AD, significantly ( p < 0.001) improved mini-mental state examination (MMSE) score, a test for measuring cognitive criteria in human subjects [ 128 ].…”
Section: Probiotics Involved In Obviation Of Alzheimer’s Disease Progression and Amelioration Of Cognitive Conditionsmentioning
confidence: 99%